Help for the haunted ebook A novel. - Searles, John (2024)
An orphaned teen investigates the deaths of her demonologist parents in this occult mystery and coming of age tale by a New York Times –bestselling author. "A dazzling, dark portrait of a troubled family beset by the supernatural. Searles ratchets up the tension with every passing chapter, and delivers authentic and well-earned scares—all written through the lens of a lonely teenager searching for answers. The result is a novel both frightening and beautiful." —Gillian Flynn Sylvie Mason's parents have an unusual occupation: helping "haunted souls" find peace. After receiving a strange phone call late one snowy night, they are lured to an old church on the outskirts of town, where Sylvie falls asleep in the car and is awoken by the sound of gunshots. Orphaned on that night, Sylvie comes under the care of her reckless, distant older sister, still living in the rambling Tudor house that guards the relics of her parents' past. As she pursues the mystery of their deaths. Sylvie's story weaves back and forth between the time leading up to the murders and the months following, uncovering the truth of what happened that night—and the secrets that have haunted her family for years. A Boston Globe Best Crime Novel of the Year An Entertainment Weekly Top Ten "Must List" Winner of the American Library Association's Alex Award Publishers Weekly , Library Journal , and Booklist starred reviews "I was completely consumed by Help for the Haunted ; I read it in one sitting. I just can't decide what I loved the most: its perfectly pitched teenage narrator; the ghost story that kept me riveted; the thriller that made me say, Oh, just one more chapter." —Jodi Picoult, New York Times bestselling author of Lone Wolf and The Storyteller "Searles craftily uses the conventions of the horror novel to cast light on the troubled dynamics at work inside a family, as well as the pressures from the outside world. His novel is both a suspenseful page turner and a provocative look at what it means to be haunted." — The Columbus Dispatch